PENANAMAN KESADARAN DAN TANGGUNGJAWAB TERHADAP LINGKUNGAN HIDUP MELALUI GREEN SCHOOL DI SD NEGERI DEMAKAN 02 TAHUN PELAJARAN 2014/2015 - Pranichayudha Rohsulina; Muhamad Husyain Rifai; Meidawati Suswandari (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2015)
Abstract This devotion aims to instill awareness and responsibility towards the environment in elementary school students. This activity was conducted in 02 primary schools with class participants Demakan 3, 4, and 5 in groups. Service activities is carried out through four stages, includes the extension (socialization), implementation, monitoring, and evaluation of results. Results devotion shows that primary school Demakan 02 Sukoharjo related to green school in the school can be taken several conclusions are: 1) There is the awareness and responsibility of environmental awareness green in SD N Demakan 02 Sukoharjo. 2) Farming with students of all ages to encourage their interest in nature and enthusiasm early in life. 3) This devotion succeeded yield as much as 110 pot polybag. Keywords: green school, awareness, responsibilityAbstract This devotion aims to instill awareness and responsibility towards the environment in elementary school students. This activity was conducted in 02 primary schools with class participants Demakan 3, 4, and 5 in groups. Service activities is carried out through four stages, includes the extension (socialization), implementation, monitoring, and evaluation of results. Results devotion shows that primary school Demakan 02 Sukoharjo related to green school in the school can be taken several conclusions are: 1) There is the awareness and responsibility of environmental awareness green in SD N Demakan 02 Sukoharjo. 2) Farming with students of all ages to encourage their interest in nature and enthusiasm early in life. 3) This devotion succeeded yield as much as 110 pot polybag. Keywords: green school, awareness, responsibility